BERTAHAN DI LINGKARAN DAMPAK ERUPSI MERAPI: KEHIDUPAN SOSIAL-EKONOMI MASYARAKAT PEDESAAN DI KECAMATAN TURI, PAKEM DAN CANGKRINGAN, 1960an-2010 - , RIA RETNO WULANSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mount Merapi is the most active volcano on the island of Java, it is very interesting to be an object of research from different disciplines, one of which is historical science. Mount Merapi is not only resulting disaster but also giving benefit for society of around it. The research in this essay is using a historical perspective in time span 1960 â 2010 and it is placing mount Merapi as natural phenomena that affect the socio-economic life of society in Turi, Pakem, and Cangkringan. This researchis using historical method with five stages: topic selection, search and collection of resources for both documents and interviews, verification or criticism of sources that include internal criticism and external criticism to test the validity and accuracy of the source, interpretation: interpretation and compilation of facts that are still scattered in chronological order, and the last is writing in descriptive narrative. The observations is focused on the danger level of volcanic activity and agricultural production statistics to see the impact of the volcanic activity of Merapi. The results of this research is that the volcanic activity of Merapi during period 1960-2010 brought a significant impact on the socio-economic life of society. That change can be seen with the growing awareness of education, it also arises because the increasing economic status of the people, especially those who have farms Salak in district Turi.The volcanic soil is suitable for crop land Salak, so the majority of people in the district Turi are planting Salak. Turi became a major supplier of salak needs in Sleman. Moreover, social change also looked after the eruption that is the uniformity of status among members of society. They have a house at the same price and vehicles that are not much different. They uniformly have a home at the same price and also vehicles that are not much different. It is resultingnot difference between the upper class, middle and bottom. Furthermore, in the economic sector, volcanic material is causing changes in the husbandry: from shepherd changes to cage. Moreover volcanic material also creates new economic resource for the community. It can be seen, there aremini museum in former their house which buried vulcanic materials. Keywords: socio-economic life, the eruption of Merapi.